TECHNOLOGY USAGE AND COMPETITIVE ADVANTAGE IN NIGERIA’S DEREGULATED PETROLEUM DOWNSTREAM SECTOR - ANYAOGU, SUNDAY ONYEKOZURU; OKUNDALAIYE, HENRY (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The study focused on the role of technology usage in fostering competitive advantage in Nigeria’s deregulated petroleum sector. For technology usage, the study focused on solar powered solutions, digital payment systems, and truck-tracking solutions. The study also focused on 3 petroleum organizations operating in the downstream sector. The study was underpinned by the resource-based view theory with a primary emphasis on competitive advantage. A simple random sampling technique was adopted to select 200 participants from the selected organizations. Questionnaire was the only source of data collection instrument. The data was analyzed with the aid of SPSS (Version 24). Regression analysis was adopted to determine the relationships. The findings showed that solar-powered solutions, digital payment systems, and truck-tracking solutions all have a significant impact on competitive advantage in Nigeria’s deregulated petroleum downstream sector. The study recommends the integration of solar-powered solutions, the expansion of digital payment systems, and the incentivization of partnerships for advanced technology adoption in Nigeria’s deregulated petroleum downstream sector. The government should further create an innovation fund and regulations to support truck tracking and real-time inventory management, enhancing efficiency, transparency, and competitiveness